Peningkatan Keterampilan Berbicara Teks Analytical Exposition dengan Teknik Pemodelan pada Siswa Kelas X2 SMAN 1 Kalitidu - Nur Italusanti; Christiana Evy Widyahening (Jurnal Syntax Admiration, 2024)
The purpose of this study is to increase student learning activities in learning the speaking skills of grade X2 students of SMAN 1 Kalitidu after participating in learning with modeling techniques. This study uses a class action research (PTK) design which is defined as a form of reflective study carried out to improve the rationality of the actions taken and improve the conditions in which practice is carried out. This class action research uses two cycles, namely cycle I and cycle II. Cycle I consists of (1) action plan, (2) action implementation, (3) observation, and (4) reflection. Through observations of student participation in modeling activities, this study shows that this approach successfully improves students' ability to understand, analyze, and compile analytical exposition texts effectively. Thus, modeling techniques can be a useful strategy in improving students' speaking skills in the context of analytical exposition texts in the school.